Pendidikan Spiritual Pada Anak: Studi Pemikiran Abdullah Nashih Ulwan (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
This research is grounded in Abdullah Nashih Ulwan's concept of the importance of providing spiritual education to children. This education equips them with moral foundations, values, and mental resilience to face the rapid and complex developments of the times. Amidst the influx of information and diverse challenges, spiritual education helps children understand deeper life purposes, recognize universal values such as justice, peace, and goodness, and attain inner tranquillity in coping with pressure and uncertainty. This research aims to uncover Ulwan's thoughts on the vision, mission, and objectives of children's spiritual education, as well as the materials and methods applied. This study employs a qualitative method with a literature review approach, where research data are obtained from various sources such as journals, books, and relevant academic works, and then analyzed deductively to obtain valid information. The research findings indicate that according to Ulwan, the vision and mission of spiritual education are to prepare children to be firm in their Islamic faith, consistent in worship, and have good relationships both vertically (with Allah) and horizontally (with others). The educational materials include concepts of monotheism, devoutness, piety, worship, awareness of Allah's supervision, love for the Prophet and his family, love for reading the Quran, and understanding of halal and haram after gaining intellect. Educational methods include exemplification, habituation, advice, attention or supervision, and punishment.
Keywords: Spiritual Education; Children; Abdullah Nashih Ulwan